Effect of Treatment Complications on the Outcomes in Adult Spinal Deformity: A Decision Analysis Approach. Issue 1 (April 2016) - Acaroglu, Emre; Güler, Ümit Özgür; Yavuz, Aysun Çetinyürek; Yavus, Yasemin; Ayhan, Selim; Sabat, Montse Domingo; Pellise, Ferran; Perez-Grueso, Francisco Javier Sanchez; Alanay, Ahmet; Obeid, Ibrahim; Kleinstuck, Frank
Introduction: Treatment of adult spinal deformity (ASD) is known to be associated with a fairly high rate of complications whereas the impact of these complications on treatment outcomes is less well known. Aim of this study is to analyze the impact of treatment complications on outcomes in ASD using a decision analysis (DA) model. Material and Methods: From an international multicentre database of ASD patients (968 pts), 535 who had completed 1 year follow-up (371 non-surgical –NS), 164 surgical –S), constitute the population of this study. DA was structured in two main steps of: 1) Baseline analysis (Assessing the probabilities of outcomes, Assessing the values of preference –utilities-, Combining information on probability and utility and assigning the quality adjusted life expectancy (QALE) for each treatment) and 2) Sensitivity analysis. Complications were analyzed as life threatening (LT) and non-life threatening (NLT) and their probabilities were calculated from the database as well as a thorough literature review. Outcomes were analyzed as improvement (decrease in ODI > 8pts), no change and deterioration (increase in ODI > 8pts). Death/complete paralysis was considered as a separate category. Results: All 535 patients (371 NS, 164 S) could be analyzed in regard to complications. Overall, there were 78 NLT and 12 LT complications and 3 death/paralysis. Surgical treatment was significantly more prone to complications (31.7% versus 11.1%, p  < 0.001) (Table 1 a). On the other hand, presence of complications did not necessarily decrease the chances of improvement, surgical patients tending to rate better in this respect (Table 1b). Likewise, QALE was not particularly affected by the presence or absence of complications regardless of the type of treatment (Table 1c). Conclusion: This study has demonstrated that surgical treatment of ASD is more likely to cause complications compared with non-surgical treatment. On the other hand, presence of complications neither has a negative impact on the likelihood of clinical improvement nor affects the QALE at the first year detrimentally.